Membangun Kesadaran Mempelajari Bahasa al-Quran Di Desa Bengkes Kecamatan Kadur Kabupaten Pamekasan - Supriyadi, Moh.; Holis, Nur; Zidan, Moh. Hamdan Yazid; Hannani, Rifqi; Sirojuddin, Sirojuddin (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2024)
Talking about Islamic education, of course it cannot be separated from the Arabic language. As the language of the Qur'an and Sunnah which is the main source for understanding Islamic religious law, of course Arabic is one of the languages that must be mastered or at least understood by Muslims. As stated in the Qur'an: "Indeed, we have revealed the Qur'an in Arabic so that you can understand it. (Q.S. Yusuf: 2). Sayyidana Umar bin Khattab also emphasized in his words "learn Arabic, because in fact Arabic is part of your religion". Arabic and the Koran are like two sides of a coin that cannot be separated from each other. Studying Arabic is a mandatory requirement for mastering the contents of the Koran, and studying the language of the Koran means learning Arabic. Thus, the role of Arabic is not only as a means of human communication, but also as a means of communication between people who believe in Allah in the form of prayer, du'a and so on.